Movimentos sociais e a CUFA-CE: uma análise da construção da identidade negra no basquete de rua - Silva, Cristiane Sousa da (2012)
This dissertation analyzes the formation of black identity of the girls and boys in the Street Basketball on the street where CUFA-Ce is placed. Aimed to identify the discourses and conceptions of the students against the black identity and contribute to studies on ethno-racial identity and black non-formal space. The research used as instruments of data collection observation and semi-structured interviews. The research subjects were students , leaders and coordinators at CUFA-Ce. The fieldwork was conducted in two bases CUFA-Ce, a neighborhood in the Barroso District in Fortaleza and another in the city of Sobral. Content analysis was used for the interpretation of the interviewees' statements collected in the field research. For the results, noting that at CUFA it's not identified as a black movement but , as black in motion, so there is a connection with thegovernmental instances ,private and civil society characteristic of the New Social Movements. Regarding the "Is street basketball a black's thing?" Stands out as one of the channels for the formation and affirmation of identity as being black, however, assume a configuration despite limited regarding after-school street basketball bases surveyed which mainly point is the visibility of black youth through LIIBRA helping to raise their self-esteem. In the category 'identities by others and by themselves "can infer the first black identity the students those formed from the gaze of the other. Secondly, the absence - in the classes of street basketball - a pedagogical intervention with racial, however, does not stimulate the debate on ethnic-racial issue and the construction of black identity in the bases studied in CUFA-Ce.